Concepts and solutions to overcome the refraction problem in terrestrial precision measurement - Ingensand, Hilmar (Geodesy and Cartography, 2012)
Refraction is a detrimental problem in terrestrial optical measurements and can be regarded as major source of systematic errors in the precise determination of distances and directions. In general, refraction is a function of the density inhomogeneities of the propagation medium. As the “classical” method of temperature-gradient determination, it does not meet the requirement of a representative integral determination of the refractive index gradient fi eld. At the Institute of Geodesy and Photogrammetry of the ETH Zurich, two methods to determine and correct the refraction infl uence have been developed further during the last few years. One approach focuses on determining the refractive index gradient in measuring the turbulence of the air by scintillometry or CDD-based image processing, which is presently the key technology in tracking tacheometers and digital levels. Turbulence is a measure of the energy in the heat exchanging process and can be converted by the Monin-Obukov-Similarity into temperature gradients. Th e advantage of optical scintillation measurements is to derive line-averaged-turbulence parameters of the atmospheric surface layer. Another challenging approach was the successful development of a compact laser-dispersometer at the ETH, which could be a component of actual geodetic instruments in the future. A dispersometer theodolite, based on the dual-wavelength method for dispersive air, is capable of refraction-free direction measurements. Th e results of both technologies, turbulence determination and dispersometry, will be presented and discussed in this paper.Refrakcijos mažinimo preciziniuose žemės paviršiaus matavimuose sprendimai bei koncepcijosSantrauka. Refrakcija – esminė problema optiniuose žemės paviršiaus matavimuose ir yra laikoma pagrindine sistemingųjų paklaidų priežastimi nustatant atstumą bei kryptį. Bendrąja prasme refrakcija yra tankio nevienalytiškumo šviesos sklidimo terpėje funkcija. Kadangi „klasikinis“ temperatūrinio gradiento nustatymo metodas neatitinka reikalavimų, keliamų nustatant tipinį integralųjį atspindžio indekso gradiento lauką, pastaraisiais metais Ciuricho ETH Geodezijos ir fotogrametrijos institute buvo sukurti du refrakcijos įtakos tyrimo bei koregavimo būdai. Vienu būdu atspindžio indekso gradientas randamas matuojant oro turbulenciją scintilometriškai ar apdorojant CCD (Charge Coupled Device) vaizdą. Tai dabar pagrindinė tacheometrų bei skaitmeninių nivelyrų stebėjimo technologija.Turbulencija yra energijos šilumos mainuose matas. Monino ir Obuchovo panašumo metodu iš turbulencijos gali būti apskaičiuotas temperatūrinis gradientas. Optinės scintiliacijos matavimų pranašumas yra vidutinių turbulencijos parametrų radimas tiriant atmosferinio paviršiaus sluoksnį. Kitas įdomus būdas tapo prieinamas sukūrus lazerinį dispersometrą ETH. Jis ateityje galėtų tapti serijinių geodezinių prietaisų dalimi. Dispersometrinis teodolitas, kurio veikimo principas grindžiamas dvigubojo bangos ilgio sklindančiame ore metodu, matuojant padeda išvengti refrakcijos. Straipsnyje aptarti abiejų minėtųjų technologijų – turbulencijos nustatymo bei dispersometrijos rezultatai.First published online: 03 Aug 2012